Conservative Surgical Treatment of a Case of Placenta Accreta - Biyik, Ismail; Keskin, Fatih; Keskin, Elif Usturali (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Placenta accreta syndromes are associated with increased maternal mortality and morbidity. Cesarean hysterectomy is usually performed in cases of placenta accreta syndrome. Fertility sparing methods can be applied. In the present study, we report a successful segmental uterine resection method for placenta accreta in the anterior uterine wall in a cesarean section case. A 39-year-old woman underwent an elective cesarean section at 38 + 2 weeks. A placental tissue with an area of 10 cm was observed extending from the anterior uterine wall to the serosa, 2 cm above the uterine incision line. The placental tissue was removed with the help of monopolar electrocautery. The uterine incision was continuously sutured. The patient was discharged on the second postoperative day. The placental pathology was reported as placenta accreta. The American College of Obstetricians and Gynecologists (ACOG) generally recommends cesarean section hysterectomy in cases of placenta accreta because removal of placenta associated with significant hemorrhage. Conservative and fertility sparing methods include placenta left in situ, cervical inversion technique and triple-P procedure. There are several studies reporting that segmental uterine resection is performed with and without balloon placement or artery ligation. Segmental uterine resection may be an alternative to cesarean hysterectomy to preserve fertility or to protect the uterus in cases of placenta accreta when there is no placenta previa.
Keywords: placenta accreta; cesarean delivery; hysterectomy prevention